An electrochemical paper-based analytical sensor for one-step latex protein detection. Issue 5 (15th February 2022) - Mettakoonpitak, Jaruwan; Junkong, Preeyanuch; Saenonphut, Aphiwan; Kwamman, Tanagorn; Siripinyanond, Atitaya; Henry, Charles S.
Abstract : A proposed simple electrochemical paper-based analytical sensor offered one-step latex protein detection by measuring remaining copper after online protein complexation Abstract : Exposure to natural rubber latex (NRL) can result in sensitivity to NRL protein with resulting allergic reactions. Low-cost, portable, simple, sensitive analytical tools for NRL protein measurements are needed for rapid and accurate assessments of allergenic risks at the point-of-care (POC) instead of using traditional methods that require large and expensive instruments, long-time analysis, and complex sample preparation steps. Here, an electrochemical paper-based analytical device (ePAD) is presented by combining sample preparation and electrochemical detection within a single device to offer a one-step NRL analysis. The lack of antibodies and/or enzymes against NRL makes POC analysis difficult. In this work, detection is based on electrochemical measurement of the remaining Cu after in situ protein complexation instead of more complex biological assays for the first time. Graphene screen-printed electrodes modified with 1, 10-phenanthroline and Nafion were used in the ePAD to improve Cu signal 18-fold relative to unmodified carbon screen-printed electrodes. The optimum parameters including 1, 10-phenanthroline concentration, reaction time between Cu and protein, and the starting Cu concentration were 5% w/v, 1 min, and 600 μg mL −1, respectively. In addition to short analysis time (4 min), the system selectivity indicated no other interfering species affecting protein detection. The proposed ePAD achieved an LOD of 3.0 mg dL −1 and a linear range of 10.0–200.0 mg dL −1 . Finally, the proposed sensors were applied for NRL protein detection and the results were not significantly different from the traditional Lowry method at 95% confidence.